PERAN QUANTUM LEARNING DALAM MENINGKATKAN MOTIVASI BELAJAR MATEMATIKA SISWA - Anisaul Khasanah, Binti; Nurmitasari, Nurmitasari (Bappeda Kabupaten Pringsewu, 2018)
Motivation to learn math is a process that determines the level of activity, intensity, consistency, and general direction of student activities in learning mathematics. Students who have strong motivation, will have a lot of energy to do learning activities so that their learning achievement will be more optimal. To increase student's motivation to learn the need for stimuli and support from outside one of them by applying the appropriate learning approach in teaching and learning process in class. One of the learning approaches that can improve students' math motivation is the Quantum Learning approach.